Atherosclerotic Renal Artery Stenosis Prevalence and Correlations in Acute Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Interventions: Data From Nonrandomized Single‐Center Study (REN‐ACS)—A Single Center, Prospective, Observational Study. Issue 10 (12th October 2015) - Burlacu, Alexandru; Siriopol, Dimitrie; Voroneanu, Luminita; Nistor, Ionut; Hogas, Simona; Nicolae, Ana; Nedelciuc, Igor; Tinica, Grigore; Covic, Adrian
Abstract : Background: We are the first to evaluate the prevalence of renal artery stenosis (RAS) in consecutive patients with acute myocardial infarction (AMI) referred for primary percutaneous coronary intervention from a single tertiary center. As a novelty, we assessed hydration and metabolic status and measured arterial stiffness. We elaborated a predicting model for RAS in AMI. Methods and Results: One hundred and eighty‐one patients with AMI underwent concomitantly primary percutaneous coronary intervention and renal angiography. We obtained data on demographics, medical history, cardiovascular risk factors, echocardiography, Killip class, and blood tests. In the first 24 hours post–primary percutaneous coronary intervention, we assessed bioimpedance through Body Composition Monitoring ® and arterial stiffness through pulsed‐wave velocity, SphygmoCor ® . Significant RAS (>50% lumen narrowing, RAS+) was present in 16.6% patients. In the RAS+ group we recorded significantly higher stiffness, CRUSADE score and dehydration, and more women with higher prevalence of multivascular coronary artery disease and heart failure. In our multivariate models, variables independently associated with RAS+ were previous percutaneous coronary intervention, low estimated glomerular filtration rate, multivascular coronary artery disease, and total/extracellular body water. These models had good specificity and low sensitivity. Conclusions: We observed that RAS+ AMI patients have a particular hydration, metabolic, and endothelial profile that could generate more future major adverse cardiac events. Hence, renal angiography in AMI should be considered in specific subsets of patients. Clinical Trial Registration: URL:https://www.clinicaltrials.gov/ . Unique identifier: NCT02388139.